Fuentes y componentes del crecimiento de la economía peruana, 1950-1990 - Seinfeld, Janice (1995)
Owing to the impossibility of explaining the abrupt changes in the Peruvian economy, especially since 1968, using traditional variables (physical capital and workforce), this piece attempts to do so by applying fresh ones (human capital, government spending and real liquidity). These provide an explanation for a substantial part of the function of production in the Peruvian economy between 1960 and 1990. The use of these variables is grounded in the models of growth with endogenous technical progress, which suggest that an economy's growth does not depend on any single factor but a combination of them. The study confirms this fact for readers.